Incompatibility Selected Dwarf Rootstock and Scion of Citrus sp. regard to Abiotic Stress Tolerant - Norry Eka Palupi; Moch. Dawam Maghfoer; Nunun Barunawati; Didik Hariyono (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
This study aims to determine the response’s incompatibility of selected dwarf citrus rootstock after treated by abiotic stresses such as drought, waterlogging, and acidity on a scion. The results of this study was selected seedlings for sub-optimal lands in Indonesia with dwarf growth characteristic and compatible with the grafted-scion. The preliminary study has shown that there were 3 (three) selected rootstock accessions with dwarf characteristics, namely Citromello (Cit), Volkameriana (Volk), and Cleopatra Mandarin (CM). The seeds of these accessions were treated with 8% Polyethylene Glycol (PEG), 150% FC; 9 mM Al2SO4 at eight months after planting. Each rootstock was grafted with Pontianak orange (C. nobilis var. microcarpa). The results showed that Citromello (Cit) and Volkameriana (Volk) are incompatible rootstock and dwarf potential seedling. However, Cleopatra Mandarin has a compatibility with the grafted scion and is tolerant of abiotic stress treatments. The effect of abiotic treatment on Citromello resulted in 15% higher root length higher than other accessions. Furthermore, this variety has 40% dry weight and 25% lateral root numbers, respectively, by Al2SO4 and PEG. Meanwhile, Volkameriana had the 40% higher number of leaves.